SISTEM PAKAR PENILAIAN PENGUASAAN MATERI PELAJARAN BERBASIS WEBSITE DENGAN METODE BAYESIAN NETWORK (Studi Kasus di SMA Angkasa Yogyakarta) - Dewi, Ni Kadek Ceryna; Honggowibowo, Anton Setiawan; Nugraheny, Dwi (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
School is a place to study to implement the learning process. However, along with the development of teaching and learning technologies now can be done outside of school one of them with online media. Students at the school will usually feel a saturation point with the delivery of material in class with the different character of the teacher. For it is made a program that could provide a new learning method. Bayesian Network Methods is a Directed Acyclic Graph (DAG) and comes with a Conditional Probability Distribution Table (CPT) for each node. Bayesian Network Methods is running on the calculations to find the value of the results of the examination of the student. From the research that has been conducted on the